2023
DOI: 10.3233/wor-220159
|View full text |Cite
|
Sign up to set email alerts
|

Managers’ and employees’ experiences of how managers’ wellbeing impacts their leadership behaviours in Swedish small businesses

Abstract: BACKGROUND: There is a growing interest in managers’ wellbeing due to the observed associations between their wellbeing and leadership behaviours, and between leadership behaviours and employees’ wellbeing. However, it is still unclear how managers’ wellbeing influences their practiced leadership across different workplace contexts, which specific behaviours are affected, and how this varies across time. OBJECTIVE: The purpose of this study was therefore to explore managers’ and employees’ experiences and perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 64 publications
1
1
0
Order By: Relevance
“…Since handling high demands requires energy (Bakker & Demerouti, 2007 ) and drains managers’ resources, this may bring short-term variations in managers’ wellbeing. This finding is in agreement with existing empirical evidence that highlights daily fluctuations in job demands and resources (Bakker, 2014 ) and fluctuations in managers’ wellbeing (Ahmadi et al, 2022 ; Barnes et al, 2015 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Since handling high demands requires energy (Bakker & Demerouti, 2007 ) and drains managers’ resources, this may bring short-term variations in managers’ wellbeing. This finding is in agreement with existing empirical evidence that highlights daily fluctuations in job demands and resources (Bakker, 2014 ) and fluctuations in managers’ wellbeing (Ahmadi et al, 2022 ; Barnes et al, 2015 ).…”
Section: Discussionsupporting
confidence: 92%
“…It is worth mentioning that these resources may also be influenced by leadership behaviours and the structure of the organization. In a recent study, Ahmadi et al ( 2022 ) found that factors that can be affected by managers’ wellbeing include the working climate, work relations, and interaction with employees as well as managers’ own performance and achievement of results. In other words, these factors may be both consequences and antecedents of managers’ wellbeing, and might be influenced both by managers’ behaviours and by the organizational context of the companies.…”
Section: Discussionmentioning
confidence: 99%